WI-FI NETWORK SECURITY ANALYSIS AGAINST PACKET SNIFFING ATTACKSAT PGRI UNIVERSITY WEST SUMATRA - Fatimah, Fatimah (Universitas PGRI Sumatera Barat, 2024)
The University of PGRI West Sumatra has wi-fi which does not rule out attacks on wi-fi networks carried out by hackers. Network Security is a protector in a network system in the process of preventing unauthorized and irresponsible network users. This research includes descriptive research. Descriptive research method is a research method that aims to explain an event. This research was conducted by testing and analyzing the test results on network security using Wireshark and Ettercap applications (Kali Linux OS). The results of this study in the form of a wi-fi network security system in building A1, building B1, building D1 at University of PGRI West Sumatra is good. During the scan for hosts, the IP of the laptop victim of the packet sniffing attack was not found.